2015
DOI: 10.14324/111.444.ijsp.2015.v4.1.002
|View full text |Cite
|
Sign up to set email alerts
|

1844-2014: 170 Years of Social Pedagogy Can Greece’s Economic Crisis Highlight the Potential of Social Pedagogy?

Abstract: He has even prepared a scroll to give him, replete with titles, with imposing names.-Why have our two consuls and praetors come out today wearing their embroidered, their scarlet togas? Why have they put on bracelets with so many amethysts, and rings sparkling with magnificent emeralds? Why are they carrying elegant canes beautifully worked in silver and gold?Because the barbarians are coming today and things like that dazzle the barbarians.-Why don't our distinguished orators come forward as usual to make the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…On the one hand, social pedagogy deals with the whole life of people (all, with special emphasis on those who experience any disadvantage and vulnerability), on the other it seeks, mainly through education, to influence them, so that they can evolve personally and socially, thus constantly expanding and utilising their cognitive, emotional, collaborative and social skills at an individual and collective level. The social pedagogue's role is linked to education when it comes to children and young people and to lifelong learning with regards to adults (Eichsteller and Holthoff, 2011;Lüssi, 2008;Mylonakou-Keke, 2015aPetrie, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, social pedagogy deals with the whole life of people (all, with special emphasis on those who experience any disadvantage and vulnerability), on the other it seeks, mainly through education, to influence them, so that they can evolve personally and socially, thus constantly expanding and utilising their cognitive, emotional, collaborative and social skills at an individual and collective level. The social pedagogue's role is linked to education when it comes to children and young people and to lifelong learning with regards to adults (Eichsteller and Holthoff, 2011;Lüssi, 2008;Mylonakou-Keke, 2015aPetrie, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This article has shown that in Greece social pedagogy and social work are clearly differentiated, having created autonomous trajectories. This differentiation is clear-cut and may initially be indicated by the distinction that exists between the words 'pedagogy' and 'work', in both their conceptual and semiotic content (Mylonakou-Keke, 2015a. This distinction is also evident in their orientations, in certain goals and priorities, their epistemological identity, their methodological approaches to time, field, the way they intervene and their potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other countries are beginning to see a growing interest in social pedagogy. In Japan it is related to social education (Matsuda, Kawano & Xiao, 2016); in Greece, to new social needs arising from the current crisis (Mylonakou-Keke, 2015; Kyridis, Christodoulou, Vamvakidou & Pavlis-Korres, 2015) and in South Africa it is focused on adult education (Ismail & Cooper, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to Hämäläinen (2012), historically, social pedagogy has emerged from an idea which advanced the process of modernisation and resulted in the new societal order, characterised by the need for education to become as an intermediary in a discrepancy between individual's autonomy and the expectations of a modern society. Even though in different countries social pedagogy is perceived rather differently, according to Mylonakou-Keke (2015), analysis of social pedagogy in the context of different world locations reveals that despite space and time, social pedagogy can be noticed to possess certain common elements governing social pedagogy's philosophy, ideology, value system, theory, methodology, areas of scientific research and practice.…”
Section: Introductionmentioning
confidence: 99%